Evaluation of anaerobic digestion of food waste and waste activated sludge : soluble COD versus its chemical composition - Ma, Yingqun (2020)
The hydrolysis as an essential step in anaerobic digestion has been commonly evaluated according to the extent of soluble chemical oxygen demand (SCOD) released from biosolids. However, little information is currently available for the effect of chemical compositions of SCOD on anaerobic digestion. This study showed that the non-biodegradable, recalcitrant organics in SCOD released from food waste and waste activated sludge pretreated with fungal mash rich in various enzymes were accumulated with the prolonged hydrolysis, while the methane production was closely related to the chemical compositions of the feed. The analyses by excitation emission matrix and size exclusion chromatography-organic carbon detection-organic nitrogen detection clearly revealed that the biodegradability of SCOD and the performance of anaerobic digestion were both determined by the chemical compositions of SCOD. These in turn challenged the present practice with SCOD concentration as a sole indicator in the selection and optimization of the pretreatment methods of biosolids prior to anaerobic digestion. It is expected that this study can offer useful insights into future design, optimization and operation of anaerobic digestion system in consideration of both SCOD concentration and its chemical compositions.